Fostering the Economic Self-Reliance of Small Businesses Based on Local Potential in Makassar City - Andi Sulfati; Patta Rapanna; Hernita Hernita (Pasundan Social Science Development, 2026)
This qualitative study employed a phenomenological approach. The findings indicate that improvements in the economic well-being of small business owners in Makassar City can be achieved through strategies such as enhancing product quality, fostering innovation, utilising digital technology, practising sound business management, developing human resources, expanding partnerships, and optimising local potential. Support from the government, financial institutions and various stakeholders is also a key factor in creating competitive and sustainable businesses. Small business owners in Makassar have advantages in the form of business flexibility, the utilisation of local potential, proximity to consumers, and their contribution to job creation. However, business owners face constraints such as limited capital, poor management skills, sub-optimal innovation, and limited use of technology. Therefore, there is a need to enhance the capacity of business owners and provide ongoing support.